Aportacions de la pragmàtica a l’anàlisi del discurs - Bassols, Maria Margarida (Caplletra. Revista Internacional de Filologia, 2015)
The aim of this work is to offer some exemples of the discourse study form the point of view of the pragmatic analysis. To do this the author has begun explaining the meaning of the terms involved in it: pragmatic presupposition, conventional and donversational implication. Afterward she has applied her method to the enigmistic dialogue, the funny utterance, the political advertising, and the publicity.